Analysis of Body Odor on Students’ Learning Comfort - Siahaan, Jeta (Lontara Digitech Indonesia, 2025)
Comfort in the learning process plays a crucial role in supporting the achievement of optimal learning outcomes among university students. However, certain aspects of the learning environment are often overlooked despite their significant impact, one of which is the presence of body odor. This condition may disrupt concentration, reduce psychological comfort, and negatively affect social interactions among students during academic activities. Based on this phenomenon, this study aims to examine the relationship between body odor and students’ level of learning comfort in higher education settings. The research adopts a quantitative approach using a survey method, with questionnaires employed as the primary data collection instrument. The research sample consists of 36 students selected through purposive sampling, a technique that involves choosing participants based on specific criteria relevant to the study objectives. Data were analyzed using correlation analysis to determine the strength and direction of the relationship between body odor and learning comfort. The findings reveal a significant relationship between body odor and students’ learning comfort, particularly in terms of concentration, academic focus, and classroom atmosphere. These results underscore that personal hygiene, especially concerning body odor, is a critical factor in fostering a healthy, comfortable, and academically supportive learning environment in higher education institutions.